"Never judge a book by its cover": Generic and Promotional Variation in English and Arabic Linguistics Book Blurbs - Awad Jasim, Tahani (Al-Adab Journal, 2018)
Blurbs are short descriptions of the contents of books usually written on their back covers for promotional purposes. This study explores the rhetorical and promotional structure of back cover blurbs accompanying English and Arabic linguistics books from genre- and evaluation- analysis perspectives. To achieve the study aims, a selected corpus of 100 blurbs, divided equally into 50 from English and Arabic linguistics book blurbs, has been considered for analysis. Results have revealed that the generic structure of book blurbs is built around a five-schematic move structure for both languages’ corpora. As to the promotional structure, positive and evaluative adjectives take precedence over other lexical categories in English and Arabic corpora. The generic and promotional structure identified all contributes to the communicative function of promoting the marketing sales of books advertised. Book blurbs can be considered as an advertising discourse performing a persuasive effect on the part of potential customers to buy and read the books advertised.